If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -20 = (3x * 4) + 5 Reorder the terms: -20 + 5y = (3x * 4) + 5 Reorder the terms for easier multiplication: -20 + 5y = (3 * 4x) + 5 Multiply 3 * 4 -20 + 5y = (12x) + 5 Reorder the terms: -20 + 5y = 5 + (12x) Solving -20 + 5y = 5 + (12x) Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 5y = 5 + 20 + (12x) Combine like terms: -20 + 20 = 0 0 + 5y = 5 + 20 + (12x) 5y = 5 + 20 + (12x) Combine like terms: 5 + 20 = 25 5y = 25 + (12x) Divide each side by '5'. y = 5 + (2.4x) Simplifying y = 5 + (2.4x)
| 5x+5=85-5 | | n-12=17 | | 2t+-7-5t=11 | | -(5y+5)-(-4y-8)=0 | | 650-5p-p^2=0 | | 6(x-2)=9x-3(2x-1) | | 3-x=15 | | 5x+22=13x-58 | | x=x-x*x | | 6x+22=13x-48 | | n+38=52 | | 5x^2+x-.25=0 | | 0.80+.05(18-x)=.10(-66) | | X^2+17+42=0 | | 3x+5=4-5x | | -24c=36c | | 5x^2-16x+15x=4x-5 | | 1x+6x-7-6=12x+15 | | 2(3-x)=5(4x-1) | | 8x-2=11x+7 | | .5(5x+4)-.33(x+7)=4 | | 81+8=6+5 | | 3x+15=33 | | 8-81=5-6 | | 3(y-8)=4(2y+9) | | 2x=7+-43-8x | | 9-p=4p-11 | | 2x-10=7x-11 | | 6a-16+6a-15+6a+7=48 | | -4x+6+x=-2x+x-10 | | -3x-8+x=-4x+-10 | | c/4=16 |